CHINA DIGITAL SILK ROAD INITIATIVES DUE TO GEO POLITICS AND GEOECONOMIC IN THE SOUTH CHINA SEA OF ASEAN REGION - Hasibuan, Febri Dirgantara; Cherry, Rahmad (Lintas Cendekia Publishing, 2024)
This study is trying to seeks a more understanding regarding the China Digital Silk Road Initiatives whether is it due to Geopolitics or Geoeconomics reason. Qualitative methodology is used to describe and interpret to generate a more understanding towards China initiatives, strategy and future cooperation or conflict. The finding of this study suggest that China is using their digital silk and road initiative as an umbrella term, both to grasp their interest in geopolitics and geoeconomics. This finding explains the specific pattern of China initiative, strategy, cooperation and conflict in the south China sea region.